Sequential Administration of Carbon Nanotubes and Near-Infrared Radiation for the Treatment of Gliomas - Santos, Tiago; Fang, Xin; Chen, Meng-Tse; Wang, Weijun; Ferreira, Raquel; Jhaveri, Niyati; Gundersen, Martin; Zhou, Chongwu; Pagnini, Paul; Hofman, Florence M.; Chen, Thomas C. (Frontiers in Oncology, 2014)
The objective was to use carbon nanotubes (CNT) coupled with near-infrared radiation (NIR) to induce hyperthermia as a novel non-ionizing radiation treatment for primary brain tumors, glioblastoma multiforme (GBM). In this study, we report the therapeutic potential of hyperthermia-induced thermal ablation using the sequential administration of carbon nanotubes (CNT) and NIR. In vitro studies were performed using glioma tumor cell lines (U251, U87, LN229, T98G). Glioma cells were incubated with CNTs for 24 h followed by exposure to NIR for 10 min. Glioma cells preferentially internalized CNTs, which upon NIR exposure, generated heat, causing necrotic cell death. There were minimal effects to normal cells, which correlate to their minimal uptake of CNTs. Furthermore, this protocol caused cell death to glioma cancer stem cells, and drug-resistant as well as drug-sensitive glioma cells. This sequential hyperthermia therapy was effective in vivo in the rodent tumor model resulting in tumor shrinkage and no recurrence after only one treatment. In conclusion, this sequence of selective CNT administration followed by NIR activation provides a new approach to the treatment of glioma, particularly drug-resistant gliomas.